2009
DOI: 10.1097/htr.0b013e3181a0b15a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Leisure Participation After a Traumatic Brain Injury

Abstract: TBI has a significant negative effect on leisure participation. Leisure activities should be evaluated and included in a therapy program designed to promote reintegration into society and work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
2
48
0
4
Order By: Relevance
“…Results of this study also indicated a shift to more homebased, sedentary and isolating leisure activities after injury, which is of particular concern. Similarly, Bier et al (2009) who also explored leisure participation of individuals with TBI who were recruited from a rehabilitation program (in and out patients), found significant changes in leisure participation pre-and post-trauma.…”
Section: Impact Of Abi On Leisure Participationmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of this study also indicated a shift to more homebased, sedentary and isolating leisure activities after injury, which is of particular concern. Similarly, Bier et al (2009) who also explored leisure participation of individuals with TBI who were recruited from a rehabilitation program (in and out patients), found significant changes in leisure participation pre-and post-trauma.…”
Section: Impact Of Abi On Leisure Participationmentioning
confidence: 99%
“…Transport, in terms of both cost and distance to venues, was commonly identified as a barrier (Bier, Dutil & Couture, 2009;Douglas, Dyson, & Foreman, 2006). Activities being held at locations that were not disability-friendly, and a lack of congruence between an individual's interests and the activities offered in their region were also found to be a major influence on participation (Douglas, Dyson, & Foreman, 2006).…”
Section: Impact Of Abi On Leisure Participationmentioning
confidence: 99%
See 3 more Smart Citations